Index: The Book of Statistical ProofsStatistical Models ▷ Univariate normal data ▷ Simple linear regression ▷ Ordinary least squares

Theorem: Given a simple linear regression model with independent observations

$\label{eq:slr} y_i = \beta_0 + \beta_1 x_i + \varepsilon_i, \; \varepsilon_i \sim \mathcal{N}(0, \sigma^2), \; i = 1,\ldots,n \; ,$

the parameters minimizing the residual sum of squares are given by

$\label{eq:slr-ols} \begin{split} \hat{\beta}_0 &= \bar{y} - \hat{\beta}_1 \bar{x} \\ \hat{\beta}_1 &= \frac{s_{xy}}{s_x^2} \end{split}$

where $\bar{x}$ and $\bar{y}$ are the sample means, $s_x^2$ is the sample variance of $x$ and $s_{xy}$ is the sample covariance between $x$ and $y$.

$\label{eq:slr-mlr} X = \left[ \begin{matrix} 1_n & x \end{matrix} \right] \quad \text{and} \quad \beta = \left[ \begin{matrix} \beta_0 \\ \beta_1 \end{matrix} \right]$

and ordinary least squares estimates are given by

$\label{eq:mlr-ols} \hat{\beta} = (X^\mathrm{T} X)^{-1} X^\mathrm{T} y \; .$

Writing out equation \eqref{eq:mlr-ols}, we have

$\label{eq:slr-ols-b} \begin{split} \hat{\beta} &= \left( \left[ \begin{matrix} 1_n^\mathrm{T} \\ x^\mathrm{T} \end{matrix} \right] \left[ \begin{matrix} 1_n & x \end{matrix} \right] \right)^{-1} \left[ \begin{matrix} 1_n^\mathrm{T} \\ x^\mathrm{T} \end{matrix} \right] y \\ &= \left( \left[ \begin{matrix} n & n\bar{x} \\ n\bar{x} & x^\mathrm{T} x \end{matrix} \right] \right)^{-1} \left[ \begin{matrix} n \bar{y} \\ x^\mathrm{T} y \end{matrix} \right] \\ &= \frac{1}{n x^\mathrm{T} x - (n\bar{x})^2} \left[ \begin{matrix} x^\mathrm{T} x & -n\bar{x} \\ -n\bar{x} & n \end{matrix} \right] \left[ \begin{matrix} n \bar{y} \\ x^\mathrm{T} y \end{matrix} \right] \\ &= \frac{1}{n x^\mathrm{T} x - (n\bar{x})^2} \left[ \begin{matrix} n \bar{y} \, x^\mathrm{T} x - n \bar{x} \, x^\mathrm{T} y \\ n \, x^\mathrm{T} y - (n \bar{x})(n \bar{y}) \end{matrix} \right] \; . \end{split}$

Thus, the second entry of $\hat{\beta}$ is equal to:

$\label{eq:slr-ols-b1} \begin{split} \hat{\beta}_1 &= \frac{n \, x^\mathrm{T} y - (n \bar{x})(n \bar{y})}{n x^\mathrm{T} x - (n\bar{x})^2} \\ &= \frac{x^\mathrm{T} y - n \bar{x} \bar{y}}{x^\mathrm{T} x - n \bar{x}^2} \\ &= \frac{\sum_{i=1}^n x_i y_i - \sum_{i=1}^n \bar{x} \bar{y}}{\sum_{i=1}^n x_i^2 - \sum_{i=1}^n \bar{x}^2} \\ &= \frac{\sum_{i=1}^n (x_i - \bar{x}) (y_i - \bar{y})}{\sum_{i=1}^n (x_i - \bar{x})^2} \\ &= \frac{s_{xy}}{s_x^2} \; . \end{split}$

Moreover, the first entry of $\hat{\beta}$ is equal to:

$\label{eq:slr-ols-b2} \begin{split} \hat{\beta}_0 &= \frac{n \bar{y} \, x^\mathrm{T} x - n \bar{x} \, x^\mathrm{T} y}{n x^\mathrm{T} x - (n\bar{x})^2} \\ &= \frac{\bar{y} \, x^\mathrm{T} x - \bar{x} \, x^\mathrm{T} y}{x^\mathrm{T} x - n \bar{x}^2} \\ &= \frac{\bar{y} \, x^\mathrm{T} x - \bar{x} \, x^\mathrm{T} y + n \bar{x}^2 \bar{y} - n \bar{x}^2 \bar{y}}{x^\mathrm{T} x - n \bar{x}^2} \\ &= \frac{\bar{y} (x^\mathrm{T} x - n \bar{x}^2) - \bar{x} (x^\mathrm{T} y - n \bar{x} \bar{y})}{x^\mathrm{T} x - n \bar{x}^2} \\ &= \frac{\bar{y} (x^\mathrm{T} x - n \bar{x}^2)}{x^\mathrm{T} x - n \bar{x}^2} - \frac{\bar{x} (x^\mathrm{T} y - n \bar{x} \bar{y})}{x^\mathrm{T} x - n \bar{x}^2} \\ &= \bar{y} - \bar{x} \, \frac{\sum_{i=1}^n x_i y_i - \sum_{i=1}^n \bar{x} \bar{y}}{\sum_{i=1}^n x_i^2 - \sum_{i=1}^n \bar{x}^2} \\ &= \bar{y} - \hat{\beta}_1 \bar{x} \; . \end{split}$
Sources:

Metadata: ID: P288 | shortcut: slr-ols2 | author: JoramSoch | date: 2021-11-16, 09:36.